Musculoskeletal disorders and its association with self-reported productivity: a cross-sectional study among public office-workers in Putrajaya, Malaysia - Albeeli, Ayman; Mohd Tamrin, Shamsul Bahri; Ng, Yee Guan; Karuppiah, Karmegam (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2020)
Introduction: Prevalence of musculoskeletal disorders (MSDs) among office workers found to be high worldwide, leading to considerable economic impacts and health issues. The relationship between MSDs and productivity loss is widely recognized. This study investigates the possible relationships between the self-reported musculoskeletal disorders and productivity in term of absenteeism/presenteeism and self-evaluated productivity levels during presenteeism time among office workers. Methods: Cross-sectional study was carried among office workers (n=398) in three public sector organizations in Putrajaya. Socio-demographic and productivity data were determined using self-administered general questionnaire whereas prevalence of MSDs evaluated using Cornell Musculoskeletal Disorders Questionnaire (CMDQ). Results: This study found that prevalence of MSDs symptoms among office workers in any body parts is high (83.7%), low-back pain reported the highest (58.5%) whereas thighs pain reported less prevalent MSDs symptoms (25.4%) among participants. Also, the results showed a significant association between prevalence of MSDs and productivity loss in regard with presenteeism (p<0.01). In addition, self-evaluated productivity levels of office workers during presenteeism time also found to be significantly associated with MSDs (p<0.05). Conclusions: These findings suggest that majority of office workers reported MSDs symptoms. Presenteeism was significantly affecting productivity in term of quality and or quantity of work that workers could do. One more concluded point of this study is the need for applying changes that could help in minimizing presenteeism due to MSDs so as to decrease workers productivity loss.